(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Globalization has dramatically influenced various sectors of the economy, particularly small businesses, which face both opportunities and challenges in this global landscape. This research investigates the impact of globalization on local businesses, with a focus on small entrepreneurs. Specifically, it examines how small businesses in [specific region or country] have responded to global competition, technological advancements, and international market trends. The study uses a sample size of 100 small entrepreneurs and employs quantitative research methods, including chi-square analysis, correlation, and regression, to identify the relationship between globalization and entrepreneurial success. Findings suggest that while globalization has created opportunities for market expansion and innovation, it also poses significant challenges such as increased competition and fluctuating demand.